To Speak Up or Stay Silent? A Multilevel Analysis of Whistleblowing Intentions in Professional Accounting - Gde Wisnu Wiradharma; Made Sudarma; Mirna Amirya (Fakultas Ekonomi dan Bisnis, Universitas Udayana bekerjasama dengan Ikatan Sarjana Ekonomi Cabang Bali, 2025)
Fraud poses a persistent risk to all organisations, prompting many to adopt whistleblowing systems as a key preventive mechanism. Guided by attribution theory, this study examines how individual attitudes, organisational commitment, and communal culture jointly shape whistleblowing intentions. Using a positivist, quantitative design, we surveyed 200 employees drawn from the Faculty of Economics and Business at Udayana University and the Bali Provincial Ministry of Religious Affairs. Structural equation modelling indicates that attitude (β = 0.453, p < 0.001), organisational commitment (β = 0.406, p < 0.001), and communal culture (β = 0.808, p < 0.001) each exert a positive, significant influence on the intention to report wrongdoing. Collectively, these factors explain 74.9 per cent of the variance in whistleblowing intentions (R² = 0.749; Adjusted R² = 0.745). The findings suggest that public institutions can reinforce fraud-reporting mechanisms by cultivating favourable employee attitudes, deepening organisational commitment, and aligning whistleblowing policies with local cultural norms. More broadly, the results confirm attribution theory’s premise that both internal dispositions and external contexts drive ethical reporting behaviour, offering a foundation for more effective fraud-prevention strategies.